1996
DOI: 10.1074/jbc.271.50.32040
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Preparation of Heparin Oligosaccharides Containing Antithrombin III Binding Sites

Abstract: Two new oligosaccharides were prepared from heparin by its partial depolymerization using heparin lyase I (EC 4.2.2.7) in an attempt to prepare oligosaccharides having intact antithrombin III binding sites. The oligosaccharides were purified by chromatography on the basis of both size and charge and demonstrated a high level of purity by capillary electrophoresis. One-and two-dimensional 1 H NMR spectroscopy at 500 MHz revealed the structure of each oligosaccharide. The octasaccharide and decasaccharide are ⌬U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 39 publications
1
40
0
1
Order By: Relevance
“…Highly sulfated liver-derived HS was isolated as previously described (44). Heparin oligosaccharides of 2, 4, 6, 8, 10, 14, and 20 subunits and control saccharide (decasaccharide containing the pentasaccharide antithrombin III-binding site) were synthesized or isolated as previously described (34,43). Mouse anti-E1 (11B7) and anti-E2 (16A6, 2F10, 917, and AP33) monoclonal antibodies (MAbs) have been described previously (11,49).…”
Section: Methodsmentioning
confidence: 99%
“…Highly sulfated liver-derived HS was isolated as previously described (44). Heparin oligosaccharides of 2, 4, 6, 8, 10, 14, and 20 subunits and control saccharide (decasaccharide containing the pentasaccharide antithrombin III-binding site) were synthesized or isolated as previously described (34,43). Mouse anti-E1 (11B7) and anti-E2 (16A6, 2F10, 917, and AP33) monoclonal antibodies (MAbs) have been described previously (11,49).…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies on tetrasaccharides sequences adjacent to the antithrombin-binding site have demonstrated two possible variants of AT-binding sequences, suggesting a possible role of the extensions of these sequences on binding to AT (9). Longer AT-binding sequences, such as decasaccharides, were also previously isolated (8). The influence of the position of the pentasaccharide sequence along the oligosaccharide chains together with the knowledge of the role of the residues prolonging the active sequence toward both its reducing and nonreducing side are among the major goals of current heparin research (10).…”
mentioning
confidence: 99%
“…are located at different sites along the oligosaccharide chains (7,8). The increasing interest in the development of "tailored" LMWHs and very low molecular weight heparins stimulates studies aimed at a better understanding at the molecular level the mechanisms of interaction between AT and AGA*IA-containing oligosaccharides.…”
mentioning
confidence: 99%
“…AT-binding oligosaccharides are usually obtained after partial chemical or enzymatic depolymerization of heparin and purification using affinity chromatography on an immobilized Sepharose-AT column (12). In other studies, the AT-binding oligosaccharides were isolated from LMWHs, such as enoxaparin, using a combination of orthogonal separation techniques, including gel permeation chromatography, HPLC, and AT affinity chromatography (13).…”
mentioning
confidence: 99%